Different Lenses for Studying Local Churches: A Critical Study of the Uses of Photographic Research Methods - Richter, Philip (Journal of contemporary religion, 2011)
Surprisingly, photography has rarely been used as a research method by those studying local churches, in spite of the fact that large numbers of photographs are taken in and around churches. This article discusses, with examples, a range of ways in which photography might appropriately be used in this context. It concludes that photographic research methods can potentially be used to good effect in the study of local churches. Both researcher-driven and more collaborative approaches deserve a place in the normal repertoire of methods for studying the local church. While visual research methods of this kind are unlikely to replace other types of research method, photographic research methods have the potential significantly to complement other methods, not least by empowering research subjects and viewers of research to produce or interrogate visual data themselves and thereby see the local church from a new perspective.